FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KECELAKAAN KERJA PADA PEKERJA BAGIAN PRODUKSI PT.HILON SUMATERA - Aswida Novrida Singarimbun; Dameria Gultom (JURNAL KESMAS DAN GIZI (JKG), 2019)
A work accident is something that is not desirable which can cause losses that harm the company and workers. Based on the results of the preliminary survey, at PT.Hilon Sumatera there were many workers who experienced work accidents such as needle punctures, pinched machines, slips due to negligence of workers, in a hurry, slippery floors, out of focus, and sleepiness. Quantitative research design withdesign Cross Sectional with the aim to determine the factors associated with the incidence of workplace accidents in production workers in PT. Hilon Sumatera with a population of 65 people. The sampling technique used is the total population, all populations are sampled. Retrieving data using a questionnaire measuring instrument. Data analysis was carried out by univariate analysis and bivariate analysis (Test Chi-Square) with a significance level of p-value = 0.05. The results showed that the workload with a p value was 0.043 <0.05, ergonomics with a p value of 0.017 <0.05, Housekeeping with a p value of 0.044 <0.05, and the availability of PPE with a p value of 0.000 <0.05 . The conclusion of this study is that workload, ergonomics, housekeeping, and the availability of personal protective equipment have a relationship with workplace accidents. It is recommended to companies to provide personal protective equipment in accordance with the needs of workers, place material for production materials in accordance with the capacity of the workspace, and improveinspection housekeeping.